2009
DOI: 10.1089/ten.tea.2007.0349
|View full text |Cite
|
Sign up to set email alerts
|

A New Paradigm for Local and Sustained Release of Therapeutic Molecules to the Injured Spinal Cord for Neuroprotection and Tissue Repair

Abstract: After spinal cord injury (SCI), a complex cascade of events leads to tissue degeneration and a penumbra of cell death. Neuroprotective molecules to limit tissue loss are promising; however, intravenous delivery is limited by the blood-spinal cord barrier and short systemic half-life. Current local delivery strategies are flawed: bolus injection results in drug dispersion throughout the intrathecal (IT) space, and catheters/pumps are invasive and open to infection. Our laboratory previously developed a hydrogel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(69 citation statements)
references
References 53 publications
2
66
0
1
Order By: Relevance
“…NSCs seeded in fibrin scaffolds within a chitosan channel, containing PLGA microspheres releasing dibutyryl cyclic-AMP, differentiate in vitro tob-III-tubulin positive neurons providing further confirmation of chitosan scaffold biocompatibility (Kim, Zahir, Tator, & Shoichet, 2011). Yet, scaffolds made of chitin, chitosan, and gelatinwith pore geometry of inverted colloidal crystals have been successfully used to guide the differentiation of iPS cells into neurons (Kuo & Lin, 2013).…”
Section: Chitosan Biocompatibilitymentioning
confidence: 80%
See 1 more Smart Citation
“…NSCs seeded in fibrin scaffolds within a chitosan channel, containing PLGA microspheres releasing dibutyryl cyclic-AMP, differentiate in vitro tob-III-tubulin positive neurons providing further confirmation of chitosan scaffold biocompatibility (Kim, Zahir, Tator, & Shoichet, 2011). Yet, scaffolds made of chitin, chitosan, and gelatinwith pore geometry of inverted colloidal crystals have been successfully used to guide the differentiation of iPS cells into neurons (Kuo & Lin, 2013).…”
Section: Chitosan Biocompatibilitymentioning
confidence: 80%
“…Lamininisan180-KDaglycoproteinthatplaysanimportantroleinneuronal cell adhesion, differentiation, and neurite outgrowth (Madison, da Silva, Dikkes, Sidman, & Chiu, 1987;Manthorpe et al, 1983). Two peptides of the lamin-1 molecule, namely, YIGSR (Tyr-Ile-Gly-Ser-Arg) and IKVAV (Ile-Lys-Val-AlaVal) sequences, mediate receptor-specific neural cell adhesion and are known to promote cell adhesion and neurite outgrowth, respectively (Graf et al, 1987;Kleinman et al, 1988;Pierschbacher & Ruoslahti, 1984;Sephel, Burrous, & Kleinman, 1989;Tashiro et al, 1989). Moreover, these domains enhance SC migration.…”
Section: Chitosan Surface Modificationmentioning
confidence: 99%
“…EPO has been delivered through injectable hydrogels, 37,38 gelatin, 26 and fibrin gel 27 for angiogenesis studies; however, only one study of which we are aware has locally delivered EPO and BMP2 from a porogenleached protein microbubble polyglycolic acid (PLGA) scaffold to assess bone regeneration in a calvarial defect model. 29 In another study, BMP2 was delivered from a collagen scaffold implanted in a rat calvarial defect, and EPO was injected subcutaneously at the defect site every other day for 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, nimodipine-loaded gels yielded particle size-dependent biphasic release profiles suggesting the accelerated delivery of poorly soluble drugs with tuneable release rates. In an another report, in vitro erythropoietin release studies revealed a 16 h release profile with the implant showing reduced cavitation after spinal cord injury along with enhanced neuronal number proving the potential of HAMC in neuroprotection after neural injury [2][3][4].…”
Section: S Nomentioning
confidence: 91%